Pharmacokinetics and Safety of Vilazodone in Hepatic Impairment. (July 2015) - Boinpally, Ramesh; Henry, Dahlia; Gupta, Samir; Edwards, John; Longstreth, James; Periclou, Antonia
Abstract : Vilazodone, a selective serotonin reuptake inhibitor and 5-HT1A partial agonist approved for the treatment of major depressive disorder, is extensively hepatically metabolized. The pharmacokinetics, tolerability, and safety of vilazodone were investigated in 2 trials comparing participants with hepatic impairment with healthy controls. In these phase 1, open-label, parallel-group, single-dose pharmacokinetic studies, vilazodone (20 mg) was administered to participants with mild, moderate, or severe hepatic impairment or individually matched healthy controls. Vilazodone and M17 (the major metabolite) concentrations in plasma were analyzed using validated liquid chromatography with tandem mass spectrometry. Forty-eight participants (8 each in mild, moderate, and severe hepatic impairment groups with matched healthy controls) were evaluated for pharmacokinetic analyses. All pharmacokinetic parameters in participants with mild and moderate hepatic impairment were similar to those in healthy controls. Mean Cmax and AUC0–∞ were approximately 29% and 17% lower in participants with severe hepatic impairment compared with healthy participants; values for Tmax, and t1/2 were similar between groups. Diarrhea was experienced by more participants with hepatic impairment than controls (10 vs. 5, respectively), and vomiting (4 participants) occurred only in participants with severe hepatic impairment; other adverse events were roughly equivalent between groups. Following a single, 20-mg oral dose of vilazodone, pharmacokinetics were similar in participants with mild, moderate, or severe hepatic impairment and healthy controls. No dose adjustment is needed for patients with major depressive disorder who have mild, moderate, or severe hepatic impairment.